RELIGION, NATIONALISM, AND CITIZENSHIP: Religion Majoritarian Approach (RMA) in Southeast Asia - Nurdiansyah, Rifqi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The majority religion in Southeast Asian countries transcends the realm of personal belief and holds significance beyond individual privacy. Hence, the objective of this study is to examine the influence of the predominant religion in each Southeast Asian country on the development of distinct patterns of religion, nationalism, and citizenship. This article uses a qualitative research method based on literature study. The approach used is RMA (Religion Majoritarian Approach). This study demonstrates the presence of three distinct typologies of state relations and majority religion in Southeast Asian nations. The initial categorization of the majority religion served as the foundation for civil identity and nationalism in countries such as Indonesia, Malaysia, Brunei Darussalam, Myanmar, Cambodia, and Thailand. The second typology refers to the imposition of limitations on the majority religion and its alignment with the objectives of the state, as exemplified by the cases of Laos, Vietnam, and Singapore. The third typology, dominant faiths assume the role of an informal institution that also governs the state, as exemplified by the Philippines and Timor Leste, where the Roman Catholic Church holds significant influence.